Investigation Mechanical and Microstructural Behavior of Operated and Unoperated Turbine Rotor Discs - UZUN KART, ELİF (My University, 2022)
In gas turbine engines, turbine sections are exposed to high temperature and loads during operation and therefore turbine inlet boundary is considered the most challenging for turbomachines. Ni-based super-alloys are used for turbine materials in gas turbine engines because of their superior mechanical characteristics at high temperatures. In this research, two Mar M-247 polycrystalline cast Ni-based turbine rotors, which were operated and non-operated in turbojet engine tests, had the same design and applied the same two-step aging heat treatment, were examined microstructurally and mechanically. As a result of the mechanical analysis, it was observed that the tensile strength (Rm (P): 537Mpa; Rm (G): 590 Mpa) ductility, and hardness (429 HV (P), 440 HV (G)) of the operated turbine rotor increased. In the microstructure analysis, blocky and Chinese script-like carbides and gamma prime eutectic islands were found in both turbine structures. EDS analysis showed that the carbides in the matrix are rich in Hf, Ta, and Ti, and the grain boundary carbides are rich in Cr and W.
Kullanılmış ve Kullanılmamış Türbin Rotor Disklerinin Mekanik ve Mikroyapısal Davranışlarının İncelenmesi
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); Mar M-247; Ni-based super-alloys; gas turbine turbojet engines; SUPERALLOY; EVOLUTION; HARDNESS; NICKEL